2001
DOI: 10.1103/physrevb.64.155310
|View full text |Cite
|
Sign up to set email alerts
|

Optical recombination from excited states in Ge/Si self-assembled quantum dots

Abstract: We have investigated the photoluminescence of single and multiple layers of Ge/Si self-assembled quantum dots as a function of the excitation power density. We show that the photoluminescence of the quantum dots is strongly dependent on the pump excitation power. The photoluminescence broadens and is blueshifted by as much as 80 meV as the power excitation density increases. Meanwhile, the photoluminescence associated with the two-dimensional wetting layers exhibits only a weak dependence on the pump excitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 33 publications
5
36
1
1
Order By: Relevance
“…5). Similar dependence of the width and position of the PL line from Ge(Si)/sSi islands on pumping power was observed earlier for structures with Ge(Si)/Si(001) islands [21]. Such behavior of the PL signal for Ge(Si) islands is typical for structures with the II-type (indirect in real space) optical transitions [22] and connected with bending of the energy bands due to the coulomb potential of holes accumulated in the islands.…”
Section: Contributedsupporting
confidence: 78%
“…5). Similar dependence of the width and position of the PL line from Ge(Si)/sSi islands on pumping power was observed earlier for structures with Ge(Si)/Si(001) islands [21]. Such behavior of the PL signal for Ge(Si) islands is typical for structures with the II-type (indirect in real space) optical transitions [22] and connected with bending of the energy bands due to the coulomb potential of holes accumulated in the islands.…”
Section: Contributedsupporting
confidence: 78%
“…Valence-band filling in Si/Ge dots was studied by Boucaud et al [11]. They concluded that, as a result of the large size and low aspect ratio of the dots in this system, the density of states in the dots differed from the quantum well case only by a factor of 2 (comparing dots with the same height as a given quantum well thickness).…”
Section: Resultsmentioning
confidence: 97%
“…The good germanium crystalline quality has been demonstrated by PL on Ge islands structures [17]. Fig.…”
Section: Quality Of Epilayermentioning
confidence: 98%